Pengaruh Pemberian Static Balance Exercise Terhadap Peningkatan Keseimbangan Tubuh Pada Lanjut Usia Di Posyandu Menur Vi Dan Viii Desa Makamhaji Sukoharjo - Monnika, Lina, Dwi Kurniawati, SST.FT, M.Kes (2016)
Background: Setbacks and neuromuscular morphological changes that occur in the elderly will lead to functional changes. Functional changes that occur include decreased strength and muscle contractions, decreased muscle lasticity and flexibility, as well as the speed and reaction time slow motion. This decline will further lead to a change in the ability to maintain a position including maintaining body balance. Research purposes: The pur ose of this study was to determine the effect of exercise to balance the increase in the balance in the elderly. Benefits of research: To know the Effect of Static Balance Balance Body Exercise To Increase In Elderly In Posyandu Menur VI and VIII Menur Makamhaji village Sukoharjo. Research methods: This research uses quasi-experimental, with the approach of pre and post with control group design. In this study the number of samples were divided into 2 groups: the treatment group were given training in the form of a static balance exercise and control groups without given exercise. Mechanical sampling with purposive sampling with a sample size of 80 people. Measurement of body balance in elderly with functional reach test sampling with inclusion technique. Research result: Based on the results of test Independent T-test known that p-value 0.001< 0.05, it can be interpreted that there is a static balance the effect of exercise to increase body balance. Conclusion: There is effect of static balance exercises to increase balance to the body of the elderly in Posyandu Menur VI and VIII Menur Makamhaji village, Sukoharjo.